Anodizing color coded anodized Ti6Al4V medical devices for increasing bone cell functions - Webster TJ (Dove Medical Press, 2013)
Alexandra P Ross, Thomas J WebsterSchool of Engineering and Department of Orthopedics, Brown University, Providence, RI, USAAbstract: Current titanium-based implants are often anodized in sulfuric acid (H2SO4) for color coding purposes. However, a crucial parameter in selecting the material for an orthopedic implant is the degree to which it will integrate into the surrounding bone. Loosening at the bone–implant interface can cause catastrophic failure when motion occurs between the implant and the surrounding bone. Recently, a different anodization process using hydrofluoric acid has been shown to increase bone growth on commercially pure titanium and titanium alloys through the creation of nanotubes. The objective of this study was to compare, for the first time, the influence of anodizing a titanium alloy medical device in sulfuric acid for color coding purposes, as is done in the orthopedic implant industry, followed by anodizing the device in hydrofluoric acid to implement nanotubes. Specifically, Ti6Al4V model implant samples were anodized first with sulfuric acid to create color-coding features, and then with hydrofluoric acid to implement surface features to enhance osteoblast functions. The material surfaces were characterized by visual inspection, scanning electron microscopy, contact angle measurements, and energy dispersive spectroscopy. Human osteoblasts were seeded onto the samples for a series of time points and were measured for adhesion and proliferation. After 1 and 2 weeks, the levels of alkaline phosphatase activity and calcium deposition were measured to assess the long-term differentiation of osteoblasts into the calcium depositing cells. The results showed that anodizing in hydrofluoric acid after anodizing in sulfuric acid partially retains color coding and creates unique surface features to increase osteoblast adhesion, proliferation, alkaline phosphatase activity, and calcium deposition. In this manner, this study provides a viable method to anodize an already color coded, anodized titanium alloy to potentially increase bone growth for numerous implant applications.Keywords: nanotechnology, titanium, osteoblasts, anodization